Israel and Iran A Dangerous Rivalry - Kaye, Dalia Dassa (RAND Corporation, 2011)
Israel and Iran have come to view each other as direct regional rivals. The two countries are not natural rivals; they have shared geopolitical interests, which led to years of cooperation both before and after the 1979 Islamic revolution. But their rivalry has intensified recently, particularly with the rise of fundamentalist leaders in Iran and the prospect of a nuclear-armed Iran posing grave strategic and ideological challenges to Israel.